(untitled) (Nordic Journal of African Studies, 2008)
As a result of the necessity to revitalize languages that have shown clear signs of endangerment, several proposals have been put forward by various studies (Paulston, 1994; Yamamoto, 1998; Landweer, 1998; Crystal, 2000; Hinton and Hale, 2001; Tsunoda, 2005; UNESCO, 2003; and Grenoble and Whaley, 2006), all of which appear to agree with Fishman (1991) on the centrality of the community whose language is endangered in leading the advocacy for the revival. Some other studies such as Krauss (1992), Rubin (1999), and Crawford (1996) have been very explicit on the community factor, separately arguing that the responsibility of language renewal should first rest upon the local community. However, such indigenous communities will usually have had their essence of togetherness disrupted to the extent that a concerted effort towards a goal envisaged as ‘communal’ is near inconceivable. Considering that language shift is often accompanied by a concomitant change in values, to expect local variables to provide the spark as well as sustain the fire for language revitalization is to assume that feelings of group identity remain intact for such a community when language shift takes place (which is not always the case). This article seeks to report on how factors internal to the Suba community of Kenya are affecting efforts to revitalize their heritage language. An examination of the community variables are here guided by parameters of vitality expounded in Grenoble and Whaley (2006), but with continuous references to the studies cited above. The data presented and discussed in the article is drawn from a sample of elders and adults from the Suba community. The analysis reveals, among other things, that the progress of language shift from Suba to Dholuo will most likely persist, the revitalization project notwithstanding, but partly due to factors that may be local, but well beyond the community’s control.